Transcriptomic analysis of the thyroid and ovarian stroma reveals key pathways and potential candidate genes associated with egg production in ducks - Zhiyu He; Qingliang Chen; Qingyuan Ouyang; Jiwei Hu; Zhengyang Shen; Bo Hu; Shenqiang Hu; Hua He; Liang Li; Hehe Liu; Jiwen Wang (Poultry Science, 2023)
ABSTRACT: The importance of thyroid-related genes has been repeatedly mentioned in the transcriptome studies of poultry with different laying performance, yet there are few systematic studies to unravel the regulatory mechanisms of the thyroid-ovary axis in the poultry egg production process. In this study, we compared the transcriptome profiles in the thyroid and ovarian stroma between high egg production (GP) and low egg production (DP) ducks, and then revealed the pathways and candidate genes involved in the process. We identified 1,114 and 733 differentially expressed genes (DEGs) in the thyroid and ovarian stroma, separately. The Gene Ontology (GO) analysis showed that a total of 504 and 189 GO terms were identified in the thyroid and ovarian stroma (P < 0.05). Three common GO terms were identified from the top 5 GO terms with the highest significant level in two tissues, including extracellular space, calcium ion binding, and integral component of plasma membrane. The enrichment analysis of the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that 15 and 14 KEGG pathways were significantly (P < 0.05) enriched in the thyroid and ovarian stroma, respectively. And, there were 8 common pathways, including neuroactive ligand-receptor interaction, calcium signaling pathway, ECM-receptor interaction, PPAR signaling pathway, melanogenesis, wnt signaling pathway, vascular smooth muscle contraction, and cytokine-cytokine receptor interaction. Notably, the neuroactive ligand-receptor interaction pathway was the most significantly enriched by the DEGs both in the thyroid and ovarian stroma. The interaction among DEGs enriched in the neuroactive ligand-receptor interaction and ECM-receptor interaction suggested that the thyroid may regulate ovarian development by these genes. Through integrated analysis of the protein-protein interaction (PPI) network and KEGG pathway maps, 9 key DEGs (PTH, THBS2, THBS4, CD36, ADIPOQ, ACSL6, PRKAA2, CRH, and PCK1) were identified, which could play crucial roles in the thyroid to regulate ovarian function and then affect egg-laying performance between GP and DP. This study serves as a basis to explore the molecular mechanism of the thyroid affecting ovarian function and egg production in female ducks and may help to identify molecular markers that can be used for duck genetic selection.